2020
DOI: 10.1002/anie.202008305
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Mapping Approach to Understand Carrier Relaxation Dynamics in Varied Regions of a Polycrystalline Perovskite Film

Abstract: We developed a direct mapping approach to overlay the image of a polycrystalline perovskite film obtained from the transient absorption microscope (TAM) with that from the scanning electron microscope (SEM). By mapping these imaging data pixel by pixel, we are able to observe the relaxation dynamics of the photo-generated charge carriers on varied regions of the film. The carrier relaxation dynamics contain a dominated single-exponential decay component owing to the recombination of charge carriers. The lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Femtosecond transient absorption spectra (TAS) thus become a powerful tool for identifying the phase purity in LD tin perovskite structures. 14,32 Ultrafast spectral studies on LD lead perovskite films showed the complicated interplay of excitonic, quantum, dielectric confinement effects, and energycascade kinetics between LD and higher-dimensional structures, 2,4,8,33,34 but such studies are scarce for tin perovskites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Femtosecond transient absorption spectra (TAS) thus become a powerful tool for identifying the phase purity in LD tin perovskite structures. 14,32 Ultrafast spectral studies on LD lead perovskite films showed the complicated interplay of excitonic, quantum, dielectric confinement effects, and energycascade kinetics between LD and higher-dimensional structures, 2,4,8,33,34 but such studies are scarce for tin perovskites.…”
mentioning
confidence: 99%
“…Although LD tin perovskites are promising photovoltaic materials, they also suffer from some problems such as random orientation and mixed-phase formation due to rapid nucleation during film preparation. , A vertical orientation and phase purity are desired characteristics for preparing LD PSCs with optimum performances as they can increase the diffusion length of carriers and enable efficient charge extraction; ,, on the contrary, random orientations induce asymmetric charge transport, and mixed-phase samples induce energy transfer on a picosecond time scale, with other nonradiative processes. Femtosecond transient absorption spectra (TAS) thus become a powerful tool for identifying the phase purity in LD tin perovskite structures. , Ultrafast spectral studies on LD lead perovskite films showed the complicated interplay of excitonic, quantum, dielectric confinement effects, and energy-cascade kinetics between LD and higher-dimensional structures, ,,,, but such studies are scarce for tin perovskites.…”
mentioning
confidence: 99%
“…Investigations using the above time-resolved techniques have been reported widely to demonstrate the correlation of the dynamics of charge carriers and photocatalytic activity. [178][179][180][181][182][183][184] Unarguably, the efficient separation and transfer of photogenerated charge carriers is key to improve the efficiency of PHE coupled with waste treatment. [185,186] Notably, the electron transport in photocatalysts with co-catalysts (Pt, Pd, Ni, NiS, MoS 2 , and so on) modification is often 2-3 orders faster than hole transfer, [172,187] resulting in the imbalance between PHE and wastes oxidation and eventually low efficiency of the system.…”
Section: Time-resolved Investigation On Charge Carriermentioning
confidence: 99%
“…In general, grain boundaries (GBs) inevitably exist in HOIPs synthesized by solution crystallization or vapor-based methods. , The GBs’ role in the carrier lifetimes of HOIPs such as MAPbI 3 (MA = CH 3 NH 3 + ) is not yet fully understood. Both negative and positive effects were reported previously. Our prior works have illustrated that charge carrier lifetimes significantly depend on the types of GBs. , On one side, GBs increase the electron–phonon interaction by localizing negative and positive charges at the boundaries and significantly decrease charge carrier lifetimes in Σ5(210) GBs, rationalizing the negative effect. On the other hand, GBs decrease the electron–phonon interaction by separating negative and positive charges and prolong carrier lifetimes in Σ5(310) GBs, providing an excellent explanation of the positive effect. Going beyond these two pioneering works, we have further demonstrated that point defects coupled to GBs can be detrimental to excited-state lifetimes of perovskite containing GBs, whereas they are benign in bulk MAPbI 3 .…”
mentioning
confidence: 99%